Revisión especial al área operativa de la empresa Queen Water y su incidencia en la calidad del servicio, cantón Manta, año 2013 - Mendoza Tuárez, Leticia María (2015)
This paper aims to make a special operational area to Queen Water Company review and its impact on service quality, canton Manta, 2013, for performance objectives established to verify compliance with regulations and standards to be met by the company, examine the main functions of the operating area, assessing internal control procedures regarding the quality of service and develop the related report of the special review. The use of relevant methodology yielded the result that the company has met the requirements to operate normally until now, that the organizational structure of the operational area of the factory does not reflect the current state of the same noting the absence of detailed information responsibilities to be met by employees, internal controls implemented in terms of service quality does not meet fully the principles of the system components and the COSO I resulting in a high risk level of 49%, and the detection of 7 findings indicating as a suggestion that although the company has complied with the regulations and standards is important to have a constant update in the field, designing the organizational structure of operational area defined levels of authority, also the management of the company must implement internal controls that seek to raise the level of quality of service.